Occupational structure and determinants of household income of pastoralists in Banni grasslands of Gujarat - MANJUNATHA, B L; SHAMSUDHEEN, M; SURESHKUMAR, M; TEWARI, PRATIBHA; YADAV, O P (The Indian Journal of Animal Sciences, 2019)
Migratory pastoralism is the traditional occupation of pastoralists (Maldharis) for more than 500 years and agriculture is not practised in entire Banni grasslands. The present study was conducted in Banni grasslands between 2014 and 2017 covering 280 households from 12 villages to investigate the livelihood and income dynamics. Banni buffalo based pastoralism and Prosopis juliflora based charcoal production were the primary occupations for 70 and 20% households respectively. Charcoal production was the predominant secondary occupation for 60% households. Sheep and goat rearing, handicrafts production, services and trade were the primary occupations for 2–3% households each. At least three livelihood options contributed to annual income of households. Contribution of primary occupation to annual income ranged from 38 to 93% whereas secondary occupation(s) contributed 0.3 to 42%. The analysis revealed that families owning >40 buffaloes were the richest group with net annual income of ` 12,07,429, followed by the households owning 21–40 animals with an average income of ` 6,94,008 and those engaged in trade with net income of ` 6,68,254. Households engaged in charcoal production and services earned net annual income of ` 65,059/ and ` 66,288/ respectively and were the poorest groups as majority of them did not own buffaloes and cattle. Those engaged in service sector were either in unorganized sector or were unskilled and semi-skilled labourers. Factors such as ownership of livestock (Banni buffalo and Kankrej cattle) and herd size; market access to milk collection centre and its distance from the village; and income from sale of milk and milk products, livestock (buffalo, cattle and camel), charcoal, embroidery, tourism and trade contributed significantly to the net annual income of households. Income earned from labour and sale of minor forest produce (honey and gum) were low and nonsignificant. Scientific management of rapidly expanding P. juliflora is crucial for conservation of Banni ecology and improving livelihoods. Establishment of milk collection centres in interior villages would contribute significantly in increasing incomes (upto ` 35,920/buffalo/lactation) of pastoralists.